Pengaruh Profitabilitas, Likuiditas dan Solvabilitas terhadap Kebijakan Dividen Perusahaan yang Terdaftar di Jakarta Islamic Indeks - Wati, Ema Risna; Anita, Efni; Putri, Nurrahma Sari (Universitas Batanghari Jambi, 2024)
This study aims to determine the effect of profitability represented by return on asset, liquidity represented by current ratio and solvency represented by debt to equity ratio on dividend policy represented by dividend payout ratio. The method used in this research is quantitative with associative research type. The object of research is companies listed on the Jakarta Islamic Indeks in 2020-2022. The sampling technique is purposive sampling so that there are 14 companies that are the object of research so that there are 42 observation data. The data in this study is panel data processed with the rstudio application. The results showed that return on asset has a significant negative effect on dividend payout ratio, current ratio has no significant effect on dividend payout ratio and debt to equity ratio has no significant effect on the dividend payout ratio. Simultaneously, all independent variabels have a significant effect on the dividend payout ratio. This research is useful for assessing the concept on finansial performance contained in finansial management using finansial ratios.